The Chimeric Self: A Neo Naturalist Bundle Theory of the Self - Compiani, Lucrezia (Frontiers in Psychology, 2019)
In contemporary cognitive science and philosophy of mind debate define the ontology of the Self is difficult if not downright dubious. Thus, different theories have been aiming to provide an account, especially where further neuroscientific research could be implemented. To this extent, the identity of the Self is suggested to be pinpointed by virtue of its specific set of mechanical features or brain functions, or it is considered the product of cognitive and conceptual capacities to build representations and narratives about ourselves. In this paper, I purport to show that, if our aim is to explain the ontology of the Self, we should approach it in a completely different way. If we endorse a Neo Naturalist approach we simply need to ask: what is the experience of ourselves, aside from our prejudices about subject and object? Where is it? What is identical to our first personal experience in the physical world? The answer is as much simply: our experience is identical to what experience is, namely the object which has all the properties that our experience has. Therefore, following the Spread Mind Theory (Manzotti 2017), I suggest that it is possible to put forward another way to solve the Self problem. Starting from the idea that the Self isn't just an aprioristic or transcendental form, I claim, endorsing a Neo Naturalist approach, that our experience is identical to the external objects which, thanks to a physical relation, constitutes the same experience. Thanks to an externalist explanation of the experience of the Self is possible to avoid multiple ontologies, causal foundationalism, naïve materialism and question begging about what we should explain. Clarifying the concept of the Self, as a bundle of relative objects which are identical with the experiences themselves, allows us to draw a physical ontology, based on the neutral (and natural) idea of relative existence rather than any posited concept of subjectivity.